Bumetanide for the treatment of seizures in newborn babies with hypoxic ischaemic encephalopathy (NEMO): an open-label, dose finding, and feasibility phase 1/2 trial. Issue 5 (May 2015) - Pressler, Ronit M; Boylan, Geraldine B; Marlow, Neil; Blennow, Mats; Chiron, Catherine; Cross, J Helen; de Vries, Linda S; Hallberg, Boubou; Hellström-Westas, Lena; Jullien, Vincent; Livingstone, Vicki; Mangum, Barry; et al.
Summary Background Preclinical data suggest that the loop-diuretic bumetanide might be an effective treatment for neonatal seizures. We aimed to assess dose and feasibility of intravenous bumetanide as an add-on to phenobarbital for treatment of neonatal seizures. Methods In this open-label, dose finding, and feasibility phase 1/2 trial, we recruited full-term infants younger than 48 h who had hypoxic ischaemic encephalopathy and electrographic seizures not responding to a loading-dose of phenobarbital from eight neonatal intensive care units across Europe. Newborn babies were allocated to receive an additional dose of phenobarbital and one of four bumetanide dose levels by use of a bivariate Bayesian sequential dose-escalation design to assess safety and efficacy. We assessed adverse events, pharmacokinetics, and seizure burden during 48 h continuous electroencephalogram (EEG) monitoring. The primary efficacy endpoint was a reduction in electrographic seizure burden of more than 80% without the need for rescue antiepileptic drugs in more than 50% of infants. The trial is registered with ClinicalTrials.gov, number NCT01434225. Findings Between Sept 1, 2011, and Sept 28, 2013, we screened 30 infants who had electrographic seizures due to hypoxic ischaemic encephalopathy. 14 of these infants (10 boys) were included in the study (dose allocation: 0·05 mg/kg, n=4; 0·1 mg/kg, n=3; 0·2 mg/kg, n=6; 0·3 mg/kg, n=1). All babies received at least one dose of bumetanide with the second dose of phenobarbital; three were withdrawn for reasons unrelated to bumetanide, and one because of dehydration. All but one infant also received aminoglycosides. Five infants met EEG criteria for seizure reduction (one on 0·05 mg/kg, one on 0·1 mg/kg and three on 0·2 mg/kg), and only two did not need rescue antiepileptic drugs (ie, met rescue criteria; one on 0·05 mg/kg and one on 0·3 mg/kg). We recorded no short-term dose-limiting toxic effects, but three of 11 surviving infants had hearing impairment confirmed on auditory testing between 17 and 108 days of age. The most common non-serious adverse reactions were moderate dehydration in one, mild hypotension in seven, and mild to moderate electrolyte disturbances in 12 infants. The trial was stopped early because of serious adverse reactions and limited evidence for seizure reduction. Interpretation Our findings suggest that bumetanide as an add-on to phenobarbital does not improve seizure control in newborn infants who have hypoxic ischaemic encephalopathy and might increase the risk of hearing loss, highlighting the risks associated with the off-label use of drugs in newborn infants before safety assessment in controlled trials. Funding European Community's Seventh Framework Programme.